Market Exclusivity of the Originator Drugs in South Korea: A Retrospective Cohort Study - Son, Kyung-Bok (Frontiers in Public Health, 2021)
Introduction: Generic entry is a well-known driver of competition and cost containment. Objectives: We aim to measure the market exclusivity of originator drugs and to determine what influences the entry of generics in South Korea. Methods: A list of originator drugs approved by the authority from 2000 to 2013 and their corresponding generics were paired. An event history model was applied for a statistical estimation for the duration until generic entry and to identify abbreviating or prolonging factors on the duration. Results: A total of 2,061 pairs of originator and generics were identified. The market exclusivity for the originator drugs, including NDAs and non-NDAs, has not notably changed. However, competition among non-NDAs was less common than we expected. We found delayed time to entry of generics in the long run, particularly for non-NDAs in injection forms and biologics, and this finding is partially associated with market attractiveness. Conclusion: The authority should address the delayed availability of certain types of generic drugs. The government could provide information on off-patent pharmaceuticals with no generic competition, designate their corresponding submissions as prioritized in the review process, and provide additional market exclusivity when entering the market via a long period of exclusivity.